(untitled) (Medical Forum Monthly, 2024)
Objective: To relate the study habits of medical students in Muhammad Medical College (MMC). To analyse the difference in study habits and academic achievements in male and female medical students in MMC. Study Design: Correlational comparative study design Place and Duration of Study: This study was conducted at Muhammad Medical College, Mirpurkhas from February 2018 to April 2018. Materials and Methods: Medical students of 2nd and final year were asked to fill a questionnaire regarding their study habits and academic performance after obtaining written consent from them. After fulfilling the inclusion and exclusion criteria a total of 109 students (50 from 2nd year and 59 from final year) entered the study. Results: A strong association amongst study habits and academic achievements (94.3%) was seen. There was a significant difference (p-value 0.003) among the study habits and academic achievements of male/female medical students.Female students have significantly better (p-value 0.003)study habits than their male counterparts. Conclusion: Student’s study habits are likely to affect their academic achievement.The findings of the study identified that good study habits of students contribute as learning guidelines for them leading academic achievement.